Endoscope-associated outbreak of OXA-181-carbapenemase-producing Klebsiella pneumoniae and its implications for hygiene management - Haak, Josefine; Klempien, I.; Hans, J. B.; Schaefer, S.; Meyer-Bothling, K.; Gatermann, S.; Dirks, E. E.; Konrat, K.; Arvand, Mardjan (The journal of hospital infection, 2025)
Aim - To report the epidemiologic, microbiologic and genetic investigation of a large outbreak of carbapenem-resistant Klebsiella pneumoniae associated with gastrointestinal endoscopy, including infection control interventions. - Methods - Internal and external audits of reprocessing procedure, systematic microbiological examination of reprocessed endoscopes, replacement of old endoscopes, investigation of channels of a dismantled endoscope, disinfectant efficacy testing on the outbreak strain's biofilm, and whole-genome sequencing (WGS) analysis were performed. - Findings - In the early phase of the outbreak, the outbreak strain was detected in 19 patients, 16 (84%) of whom had undergone gastrointestinal endoscopy. The strain was also isolated from a reprocessed endoscope. WGS confirmed clonal relatedness of isolates and suggested transmission between patients via contaminated endoscopes. The reprocessing was audited, old endoscopes were replaced with new ones, and systematic microbiological examination of new endoscopes was introduced. In the follow-up, the outbreak strain was isolated from a new endoscope after reprocessing. Repeat audit revealed residual moisture in endoscope channels after reprocessing. Inspection of a dismantled endoscope revealed debris and scratches in channels. Disinfectant efficacy testing revealed tolerance of the outbreak strain's biofilm to peracetic acid. The outbreak strain was isolated from 32 patients and two reprocessed endoscopes. WGS suggested patient-to-patient as route of transmission in the outbreak's later phase. - Conclusions - A multi-stage strategy was required to contain this outbreak. Microscopic analysis showed evidence of biofilm formation in endoscope channels and the outbreak strain's biofilm showed tolerance to the disinfectant used for reprocessing. Our data underscores the need for continued vigilance in infection control practices and reprocessing protocols for endoscopes.
Online verfügbar: 07. Februar 2025, Artikelversion: 07. März 2025
Gesehen am 31.10.2025